System zarządzania środkami pieniężnymi w przedsiębiorstwie - budowa i warunki optymalizacji - Śpiewak, Tomasz (Cash Management Model in an Enterprise - Creating and Terms of Optimization, 2008)
The paper focuses on cash management. The goal of cash management is to maintain the minimum cash balance that will provide the firm with sufficient liquidity and to enhance its profitability without exposing it to undue risk. Some models may be applied to management of cash. The decisions covered by the models deal with the size and timing of transfers between cash and marketable securities. The goal of my article was to create the complex system of cash management and show the way of use of the theoretical cash management models in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 569-578